Neoadjuvant chemoradiotherapy with camrelizumab in patients with locally advanced esophageal squamous cell carcinoma - Chen, Fei; Qiu, Lingdong; Mu, Yushu; Sun, Shibin; Yuan, Yulong; Shang, Pan; Ji, Bo; Wang, Qifei (Frontiers in Surgery, 2022)
Background: Neoadjuvant anti-programmed death receptor-1 (PD-1) blockade has been reported to improve the prognosis of locally advanced esophageal squamous cell carcinoma (ESCC). This study was aimed to evaluate the efficacy and safety of neoadjuvant camrelizumab plus chemoradiotherapy in locally advanced ESCC. Methods: We retrospectively enrolled ESCC patients who received camrelizumab plus chemoradiotherapy as neoadjuvant therapy before surgery from May 2019 to September 2021. Results: A total of 38 eligible patients were enrolled. The neoadjuvant treatment was well tolerated with no serious treatment-related adverse events. 36 (94.7%) patients achieved a R0 resection without hospital mortality or any other serious intraoperative complications. The objective response rate (ORR) was 63.2% and the disease control rate (DCR) was 100.0%. The major pathological response (MPR) was 50.0% and the complete pathological response (pCR) was 39.5%. With a median follow-up of 18.5 months, 6 (15.8%) patients had died. The overall survival (OS) and disease-free survival (DFS) at 12 months were 87.6% and 78.7%, respectively. Subgroup analysis demonstrated that patients who got MPR or pCR achieved improved survival, while PD-L1 expression did not reach statistically difference in predicting survival. Conclusions: Neoadjuvant camrelizumab plus chemoradiotherapy is safe and efficacious in treating patients with locally advanced ESCC.